2020
DOI: 10.1016/j.joei.2020.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of lignocellulosic biomass investigating different pyrolysis temperatures

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…The biomass showed characteristics that make it suitable for the production of bio-oil through the flash pyrolysis process, such as high HHV (17 MJ kg −1 ), higher than common biomasses, such as sugarcane bagasse (Santos et al, 2020) 13 , ash content less than 10% and volatile content similar to switchgrass 14 (Table 1 ). The heating value found was similar to other lignocellulosic biomasses, such as rice husks (17.95 MJ kg −1 ), peanut husks (20.61 MJ kg −1 ) and wheat straw (17.36 MJ kg −1 ) 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The biomass showed characteristics that make it suitable for the production of bio-oil through the flash pyrolysis process, such as high HHV (17 MJ kg −1 ), higher than common biomasses, such as sugarcane bagasse (Santos et al, 2020) 13 , ash content less than 10% and volatile content similar to switchgrass 14 (Table 1 ). The heating value found was similar to other lignocellulosic biomasses, such as rice husks (17.95 MJ kg −1 ), peanut husks (20.61 MJ kg −1 ) and wheat straw (17.36 MJ kg −1 ) 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The acidity level or pH is measured to determine the acidity of the liquid smoke. The liquid smoke produced via pyrolysis is generally acidic, with a pH value in the range of 2-4, mainly in the form of acetic acid and formic acid [16,17,18].…”
Section: Ph Valuementioning
confidence: 99%
“…Santos et al [22] reported that the bio-oil yields of sugarcane bagasse and oat hulls are improved by running the TCR system at lower reforming temperatures (500, 600, and 700°C) which reduce the enhanced cracking of organic vapors. Furthermore, TCR makes a better separation between the water phase and organic phase of the pyrolysis liquid, and this is the reason why the HHV of TCR oils are higher than fast-pyrolysis oils [23,47]. However, to determine the economic viability of the TCR process of wood and DIS, a full techno-economic evaluation is required to be done as future work.…”
Section: Product Compositionsmentioning
confidence: 99%
“…Thermocatalytic reforming (TCR) is a technology that combines intermediate pyrolysis and high-temperature reforming of volatiles in a single processing system. The organic vapors undergo cracking and reforming, and this results in bio-oil with improved physicochemical characteristics [22,23].…”
Section: Introductionmentioning
confidence: 99%